Tree growth in West African cocoa agroforestry systems: high timber yields and superior performance of natural regeneration - (:unkn) unknown (My University, 2025)
AbstractKey messageCocoa agroforestry systems (AFS) in West Africa represent an underexplored yet promising source of timber. Within these systems, species can reach a 50-cm diameter as early as 14 years of age. Naturally regenerated trees grow 10% faster than planted ones and develop a 43% greater bole volume. These findings underscore the high timber potential of cocoa AFS and confirm natural regeneration as a superior strategy for tree renewal and wood production.ContextIn West Africa, where over 80% of original forests have been converted to agriculture, finding alternative timber sources is essential. Agroforestry, prevalent across the region, offers a potential solution.AimsThis study assesses the timber production potential of trees in cocoa agroforestry systems in Côte d’Ivoire.MethodsIn 150 cocoa agroforestry plots, we (i) modelled the diameter growth of forest tree species; (ii) developed specific allometric models for cocoa AFS; and (iii) evaluated the effect of tree origin (natural regeneration vs. plantation) on growth trajectories, allometry, and bole volume.ResultsTrees can reach a diameter of 50 cm as early as 14 years of age, and a bole height of up to 8.83 m at this diameter. Naturally regenerated trees grow 10% faster annually than planted trees, reaching their minimum logging diameter up to 10 years earlier, and have a 43% greater bole volume.ConclusionNatural regeneration is a more effective strategy than planting for tree renewal in cocoa AFS, providing faster growth, greater timber volumes, and significant potential for sustainable forestry management and meeting regional timber demands.
Keywords: African Research